Seeking Truth beyond Facts: Debates on Facts and History in the Kongcongzi - Crone, Thomas (Monumenta Serica - Journal of Oriental Studies, 2023)
This article analyzes concepts of factual narration in the Kongcongzi, a text that thus far has received little scholarly attention. The author argues that the text indicates a pronounced interest in this subject, and presents different points of view. The first ten chapters of the Kongcongzi tend to manifest a lenient attitude towards narrative factuality, whereas in Chapters Twelve to Twenty-one, the distinction between facts and falsehood seems to become increasingly important. Through a comparative analysis of narratives from both groups of chapters, the author attempts to explore the protagonists’ views on the meaning and purpose of factual narration. The author also explores various conclusions that can be drawn from these insights in the context of the textual history of the Kongcongzi and our understanding of early Chinese narrative prose in general.
Created from Fastlane, Scopus look-up
Keywords: Confucian lore; early Chinese historiography; factual narration; forged texts; Kongcongzi